Human Periodontal Ligament Stem Cell-Derived Exosomes Promote Bone Regeneration by Altering MicroRNA Profiles. (19th November 2020) - Liu, Ting; Hu, Wenyun; Zou, Xue; Xu, Jingchen; He, Shushu; Chang, Le; Li, Xinyi; Yin, Yuanyuan; Tian, Mi; Li, Ziyu; Zhou, Jialiang; Jiang, Xiaoge; et al.
Abstract : The role and underlying mechanism of exosomes derived from human periodontal ligament stem cells (PDLSC) in osteogenesis are unclear. In the present study, we identified the exosomes derived from PDLSCs and found that osteogenic induction can enhance the osteogenic ability of PDLSC-derived exosomes in promoting the osteogenic differentiation of rat bone marrow stem cells (BMSCs). To investigate the underlying mechanism, we analyzed the exosomal miRNA expression profiles of undifferentiated and osteogenic differentiated PDLSCs by RNA sequencing. The results showed that seventy-two miRNAs were upregulated and thirty-five miRNAs were downregulated after osteogenic induction. The results of Gene Ontology analysis and pathway analysis demonstrated that the target genes of differentially expressed exosomal miRNAs participate in the regulation of a variety of biological processes, such as catalytic activity, protein binding, metabolic processes, cell development, and differentiation, and are enriched in osteogenic differentiation-related pathways, such as MAPK signaling, AMPK signaling, and insulin signaling pathways. Our results reveal for the first time that the exosomal miRNAs derived from osteogenic differentiated PDLSCs may promote the osteogenic differentiation of BMSCs, which provides a basis for further research on the regulatory function of exosomal miRNA of PDLSCs during osteogenesis.